RAPID ON-SITE EVALUATION (ROSE) OF SPECIMEN ADEQUACY DURING CT GUIDED FINE NEEDLE ASPIRATION OF LUNG LESIONS. (February 2015) - Solout, Alireza Khani; Parry, Jeremy; Forrest, Cynthia
Abstract : Aim: FNA is a complex multistep process, and several factors have the potential to affect specimen adequacy and the overall diagnostic yield. One of the factors which can affect specimen adequacy rate is the use of rapid on-site evaluation (ROSE). This audit aims to compare specimen adequacy in CT guided FNA of lung in two centres. Methods: At Centre 1 CT-guided FNA of lung procedures are attended by a cytotechnologist, either with or without ROSE. At Centre 2 these procedures are attended by a cytopathologist who performs ROSE. We retrospectively studied cytology reports of CT guided lung FNA during a 14-year period in two tertiary hospitals in the South Metropolitan Health Service in Western Australia. We reviewed reports on all insufficient samples in both centres. Results: In Centre 1, out of 2297 FNAs there were 195 cases of inadequate samples. In this group 179 first FNAs and 16 second FNAs yielded insufficient material for diagnosis. In Centre 2, out of 1362 FNAs there were 85 cases of inadequate samples. These included 82 first FNAs and three second FNAs. Conclusions: Our study suggests that for CT guided lung FNAs ROSE performed by a cytopathologist can significantly improve specimen adequacy.